Cancer proteomics: developments in technology, clinical use and commercialization. (August 2015) - Yeat, Nai Chien; Lin, Charlotte; Sager, Monica; Lin, Jimmy
<x xml:space="preserve">Abstract</x> In the last two decades, advances in genomic, transcriptomic and proteomic methods have enabled us to identify and classify cancers by their molecular profiles. Many anticipate that a molecular taxonomy of cancer will not only lead to more effective subtyping of cancers but also earlier diagnoses, more informative prognoses and more targeted treatments. This article reviews recent technological developments in the field of proteomics, recent discoveries in proteomic cancer biomarker research and trends in clinical use. Readers are also informed of examples of successful commercialization, and the future of proteomics in cancer diagnostics.